The polymorphism of archaeological GIS. Unfolding the archaeological dimensions of GIS - Sarris , Apostolos (Journal of Greek Archaeology, 2024)
Having travelled through more than 30 years on the chariot of GIS, archaeology has benefited significantly from its tools and functionalities, trying to identify its matching with it on both a theoretical and practical level. Independent of the applications that have been carried out, micro or macro, 2D, 3D, 4D, geostatistical or descriptive, locational, and predictive analyses or monitoring, GIS has unfolded new dynamics in archaeological research, moving away from simple mapping, visualization and geotagging to address challenging tasks of analysis that combined diverse geographic, temporal, environmental, climatic, and cultural datasets. It has been an expected evolution as the science of Geoinformatics has been accelerated through the recent developments of smart sensors and imaging technologies from space, air, land and underwater, the fusion of different datasets, the exponential increase of data that led to the rise of Big Data, and the advancement of processing algorithms though ML and AI techniques. We are experiencing the impact of the new generation of GIS in archaeology. But is the archeological community ready for the next step?